Banking Institutions Governance and Stock Market and Financial Performance - Mselmi, Aymen; Regaieg, Boutheina (International Journal of Economics and Financial Issues, 2017)
This paper examines the relationship between banking governance internal mechanisms and financial and stock market performance. To examine this relationship, we studied a sample of 11 Tunisian banks over the 2006-2013 period. Our aim is to identify the key governance variables that contribute to improving financial and market performance of Tunisian banks. The obtained results indicate that “good” governance practice codes contribute to better financial and market performance. Keywords: Banking Governance, Financial Performance, Stock Market Performance JEL Classifications: G01, G20, G30